2019
DOI: 10.1590/0074-02760190098
|View full text |Cite
|
Sign up to set email alerts
|

Previous dengue or Zika virus exposure can drive to infection enhancement or neutralisation of other flaviviruses

Abstract: BACKGROUND Dengue virus (DENV) has circulated in Brazil for over 30 years. During this time, one serotype has cyclically replaced the other, until recently, when all four distinct serotypes began to circulate together. Persistent circulation of DENV for long time periods makes sequential infections throughout a person's life possible. After primary DENV infection, lifelong immunity is developed for the infecting serotype. Since DENV and Zika virus (ZIKV) are antigenically similar, the possibility of cross-reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 23 publications
2
24
0
1
Order By: Relevance
“…The incidence of dengue has remained stable over the past few decades in Vietnam [27], and dengue seroprevalence remains high, with up to 64% of the adult population being seropositive [28]. Recent studies have suggested that while DENV is cross-reactive with ZIKV, the level of cross-neutralization and hence disease protection is limited [29][30][31]. In Vietnam, the number of ZIKV infections peaked at 219 in 2016, and has subsequently decreased, with only one reported case in 2019 [32].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of dengue has remained stable over the past few decades in Vietnam [27], and dengue seroprevalence remains high, with up to 64% of the adult population being seropositive [28]. Recent studies have suggested that while DENV is cross-reactive with ZIKV, the level of cross-neutralization and hence disease protection is limited [29][30][31]. In Vietnam, the number of ZIKV infections peaked at 219 in 2016, and has subsequently decreased, with only one reported case in 2019 [32].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Brazil has 210 million inhabitants spread over 8 million km 2 (latest United Nations Population Division estimates). In Brazil, as other Latin American countries, cocirculation of other flaviviruses such as DENV, Yellow fever virus, Bussuquara, Cacipacoré, Ilhéus, Rocio and Saint Louis encephalitis virus might elicit unique flaviviral antibody responses that impact ZIKV-specific antibody kinetics [15][16][17]. Nonetheless, longterm antibody kinetics of individuals infected with ZIKV in Brazil are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…There are no documented cases of repeated YFV infection, even in several historical cohorts [49]. Evidence also suggests that previous heterologous flavivirus exposure, for example from prior dengue virus infection, may provide partial cross protection against severe YF [43,50,51].…”
Section: Introductionmentioning
confidence: 99%